Knowledge and Attitude Regarding Euthanasia among Selected Population in Thiruvananthapuram, Kerala - Sreeja I (International Journal of Psychiatric Nursing., 2015)
Euthanasia is a term embroiled in controversy across the world. This study aimed to assess the knowledge and aitude towards euthanasia among urban population of Thiruvananthapuram district. A convenience sample of 50 was included for the study. Data were collected by cross sectional design. Knowledge and aitude was assessed using structured self report questionnaire. Results revealed that 50% of the subjects had good knowledge about euthanasia and 68% had positive aitude towards euthanasia. The study has got implication in health care practice that representatives of the general public should be included to formulate relevant policies related to euthanasia